Daptomycin Liposomes Exhibit Enhanced Activity against Staphylococci Biofilms Compared to Free Drug - Foteini Gkartziou; Maria Plota; Charikleia Kypraiou; Iti Gauttam; Fevronia Kolonitsiou; Pavlos Klepetsanis; Iris Spiliopoulou; Sophia G. Antimisiaris (MDPI AG, 2024)
The purpose of the present study was to investigate the anti-staphylococcal activity of liposomal daptomycin against four biofilm-producing S. aureus and S. epidermidis clinical strains, three of which are methicillin-resistant. Neutral and negatively charged daptomycin-loaded liposomes were prepared using three methods, namely, thin-film hydration (TFH), a dehydration-rehydration vesicle (DRV) method, and microfluidic mixing (MM); moreover, they were characterized for drug encapsulation (EE%), size distribution, zeta-potential, vesicle stability, drug release, and drug integrity. Interestingly, whilst drug loading in THF and DRV nanosized (by extrusion) vesicles was around 30-35, very low loading (~4%) was possible in MM vesicles, requiring further explanatory investigations. Liposomal encapsulation protected daptomycin from degradation and preserved its bioactivity. Biofilm mass (crystal violet, CV), biofilm viability (MTT), and growth curve (GC) assays evaluated the antimicrobial activity of neutral and negatively charged daptomycin-liposomes towards planktonic bacteria and biofilms. Neutral liposomes exhibited dramatically enhanced inhibition of bacterial growth (compared to the free drug) for all species studied, while negatively charged liposomes were totally inactive. Biofilm prevention and treatment studies revealed high antibiofilm activity of liposomal daptomycin. Neutral liposomes were more active for prevention and negative charge ones for treating established biofilms. Planktonic bacteria as well as the matured biofilms of low daptomycin-susceptible, methicillin-resistant Staphylococcus aureus (MRSA) and Staphylococcus epidermidis (MRSE) strains were almost completely eradicated by liposomal-daptomycin, indicating the need for their further exploration as antimicrobial therapeutics.